Vinblastine increases antitumor effectiveness of bleomycin - Čemažar, Maja (Radiology and oncology (Ljubljana), 1997)
In our previous vinblastine (VELBE) was shown to increase the plasma membrane fluidity. This effect of VELBE might be expolited for better transport of drugs through the plasma membrane. Bleomycin (BLM) is a highly cytotoxic drug when present inside the cells but has a hampered transport through the plasma membrane. The aim of the present study was to determine whether pretreatment with VELBE can increase the effect of BLM on intraperitoneal SA-1 tumors in mice. BLM and VELBE were used as single agents or in various combinations, i.e. VELBE and BLM injected simultanously, BLM injected 24 h before VELBE or VELBE injected 24 h before BLM. Mice survival was the end-point used for determining the effect of this combined treatments. VELBE and BLM as a single treatment significantly prolonged median survival time of study animals compared to controls. Furthermore, when VELBE and BLM were combined, all threetested combinations were more effective than VELBE or BLM as single treatments. The effect on animal survival was equal when VELBE was given 24 h after or simultanously with BLM. The longest survival, however was obtained when VELBE was injected 24 h before BLM. From these results we can conclude that the underlying mechanisms for more than additive effect of VELBE and BLM when VELBE was given 24 h before BLM could be attributed to an increased membrane fluidity, possibly in combination with a cell kinetic effect.
Keywords: fiziologija; poskusi; rak (medicina); sarkom; zdravljenje